A comparative study of mesenchymal stem cells cultured as cell‐only aggregates and in encapsulated hydrogels. (22nd October 2021) - Passanha, Fiona R.; Gomes, David B.; Piotrowska, Justyna; ,; Moroni, Lorenzo; Baker, Matthew B.; LaPointe, Vanessa L. S.
Abstract: There is increasing evidence that cells cultured in three‐dimensional (3D) settings have superior performance compared to their traditional counterparts in monolayers. This has been attributed to cell–cell and cell–extracellular matrix interactions that more closely resemble the in vivo tissue architecture. The rapid adoption of 3D cell culture systems as experimental tools for diverse applications has not always been matched by an improved understanding of cell behavior in different 3D environments. Here, we studied human mesenchymal stem/stromal cells (hMSCs) as scaffold‐free self‐assembled aggregates of low and high cell number and compared them to cell‐laden alginate hydrogels with and without arginine‐glycine‐aspartic acid peptides. We observed a significant decrease in the size of cell‐only aggregates over 14 days in culture compared to the cells encapsulated in alginate hydrogels. Alginate hydrogels had persistently more living cells for a longer period (14 days) in culture as measured by total DNA content. Proliferation studies revealed that a weeklong culture of hMSCs in 3D culture, whether as aggregates or cell‐laden alginate hydrogels, reduced their proliferation over time. Cell cycle analysis found no significant differences between days 1 and 7 for the different culture systems. The findings of this study improve our understanding of how aggregate cultures differ with or without a hydrogel carrier, and whether aggregation itself is important when it comes to the 3D culture of hMSCs.